G115 Thinking together: A pilot scheme linking paediatric and CAMHS trainees to improve collaboration and address training gaps. (24th May 2017) - Cryer, JP; Wilson, E; Conn, R; Bulwer, C; Singh, G; Oxley, C; Boyd, H; Laurent, S; Menden, M
Abstract : Background: Mental health presentations are an increasing part of the paediatric caseload and there is growing evidence that paediatric trainees feel ill-equipped to manage these patients. Only 33% of trainees we surveyed felt that their current training programme enabled them to achieve their curriculum requirements in paediatrics or mental health respectively. CAMHS services are increasingly stretched, raising referral thresholds and making the need for closer working together across disciplines paramount. Aim: A working group of paediatric and psychiatry trainees developed the concept of Thinking Together, to tackle this training gap. The scheme involves pairing paediatric and CAMHS trainees to share in each other's clinical encounters to foster a joint way of learning and working together, while fulfilling curriculum competencies that are otherwise difficult to achieve. Method: A pilot was launched in March 2016 where trainees from both specialties were paired for a period of 6 months, attending at least two clinical encounters in each setting. Curriculum competencies for both specialties were outlined in a resource pack. Trainees were encouraged to explore a variety of learning possibilities, including clinics, referral meetings and signposting their partner to other relevant clinical opportunities. Results: 30 trainees were surveyed and 16 of these completed pre and post pilot evaluation. Prior to participating in Thinking Together, 70% stated they had no experience of working in a jointly delivered paediatric/mental health clinic. 93% of participants felt that their patients benefitted from access to the jointly delivered paediatric and mental health clinics. Confidence in achieving curriculum competencies in paediatrics and mental health respectively, increased to 93% following involvement in the project. Conclusion: Our results highlighted that trainees felt they had achieved curriculum competencies in their linked specialty, while improving their capabilities in collaborative, patient-centred practice. Trainees felt the scheme benefitted both their patients and themselves, thinking together through cases and developing a greater appreciation of different professionals' roles and responsibilities. As the burden of mental health grows, with it's irrefutable link to physical well being, we feel schemes such as ours will improve understanding for future trainees between the cross over of mind and body.